Comparison of true mangrove stands in Dudepo and Ponelo Islands, North Gorontalo District, Indonesia - FAIZAL KASIM; MIFTAHUL KHAIR KADIM; SITTI NURSINAR; ZULKIFLI KARIM; ALDIN LAMALANGO (Society for Indonesian Biodiversity, 2019)
Abstract. Kasim F, Kadim MK, Nursinar S, Karim Z, Lamalango A. 2019. Comparison of true mangrove stands in Dudepo and Ponelo Islands, North Gorontalo District, Indonesia. Biodiversitas 20: 359-366. This study aimed to investigate and compare the current status of mangrove areas, as well as the composition and species diversity of mangrove stands in both regions of Dudepo and Ponelo Islands. The results showed that the mangrove areas calculated using the segmentation method in classifying image of Landsat-8 OLI (acquisition on September 2017) were 279.46 ha (Dudepo Island) and 113.35 ha (Ponelo Island) respectively. A total of 13 species of true mangrove were recorded from both islands, using survey method from 9 transect lines (TL), with a distance ranging from 40 to 210 meters (1-6 quadrats) per transect. The mean densities of trees were 2133 ± 329.78 ha-1 (Dudepo Island) and 2111 ± 234.28 ha-1 (Ponelo Island), while those of saplings and seedlings were 58 ± 13.48 ha-1 and 1425 ± 113.96 ha-1 (Dudepo Island), and 79 ± 14.51 ha-1 and 2963 ± 443.22 ha-1 (Ponelo Island). The mean diameter and basal area were 19.73 ± 10.65 cm and 84.22 ± 67.67 m2ha-1 (Dudepo Island), 17.04 ± 1.46 cm and 60.07 ± 15.12 m2ha-1 (Ponelo Island), respectively. The Importance Value Index (IVI) ranged between 3.97-114.87 (Dudepo Island) and 6.04-82.18 (Ponelo Island). The dominant and codominant species based on IVI in both islands were Rhizophora apiculata Blume and R. stylosa Griff. The indexes of diversity, richness, and evenness of mangrove species in both islands were 0.34-1.70, 0.48-1.18, 0.47-0.94 (trees), 0.00-1.10, 0.00-1.82, 0.00-1.00 (saplings), and 0.00.-1.48, 0.00-1.44, 0.72-1.00 (seedlings), respectively. The Bray-Curtis similarity index between Dudepo and Ponelo Islands, based on the overall values of community attributes, was 0.75.